1997
DOI: 10.1177/105256299702100106
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment Projects as Teaching and Learning Tools

Abstract: Quality management is a broad subject whose principles and practices are best understood when studied in the context of real-life organizations. This article describes a major quality assessment field project that serves as the integrative vehicle for an MBA curriculum. Each year the entire entering MBA class devotes a portion of 8 months to performing comprehensive quality audits of external organizations. Whereas they reinforce the principles of quality management, the field projects also require students to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Students make detailed observations and practice these skills several times during the 2 weeks. Five months later, when the graduate students are in the middle of a three-term, team-based integrated project that requires consultation with a real organization (Bloomfield & Paschke, 1997), we require them to revisit group roles and feedback by conducting a process discussion of how well their group works together. We have found that when content is central to a curriculum, it cannot be partitioned into a stand-alone course if learning is to occur.…”
Section: Integrationmentioning
confidence: 99%
“…Students make detailed observations and practice these skills several times during the 2 weeks. Five months later, when the graduate students are in the middle of a three-term, team-based integrated project that requires consultation with a real organization (Bloomfield & Paschke, 1997), we require them to revisit group roles and feedback by conducting a process discussion of how well their group works together. We have found that when content is central to a curriculum, it cannot be partitioned into a stand-alone course if learning is to occur.…”
Section: Integrationmentioning
confidence: 99%